ANALYSES ON FACTORS AFFECTING TB INFECTION IN CHILDREN LIVING AT THE SAME HOUSE WITH TB PATIENTS AT WAINGAPU PUBLIC HEALTH CENTER, EAST SUMBA REGENCY EAST NUSA TENGGARA PROVINCE - YOSEF LAKA (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2013)
Background: Tuberculosis (TB) is a major problem encountered by the majority of the world communities, particularly those living in developing countries. It is estimated that out of 100,000 people of Indonesia, 119 suffered from positive acid fast bacillus lung TB, 15% of which were children. In 2007, in East Sumba Timur Regency there were 300 adults and 242 children suffering from positive acid fast bacillus lung TB. Prevalence of lung TB in the regency was 73.3%, presumably because of the high risk of infection particularly caused by direct contact with TB patients living in the same house. The study was to find out factors affecting TB infection in children living together with lung TB patients. Method: The study was a descriptive study with cross sectional design. Sample of the study were 55 children of 0-20 years in age living in the same house with the positive acid fast bacillus lung TB patients who were undergoing medication or post medication for 1 year. The samples were obtained using a total sampling technique with questionnaires, body weighting, and TB measurement as research instruments. Data analysis used a frequency distribution table. Result: Result of the study showed that out of 55 respondents investigated, there were factors affecting the incidence of TB infection in children living at the same house with TB patients. Occupation affected knowledge (Pvalue = 0.000), behavior (Pvalue = 0.000), nutrition status (Pvalue = 0.000) and immunization status (Pvalue = 0.053), while age affected knowledge (Pvalue = 0.000), behavior (Pvalue = 0.000), nutrition status (Pvalue = 0.000), immunization status (Pvalue = 0.053), occupation density of 61.8% with a ‘moderately dense’ category, and unqualified residential condition of 58.2%. Conclusion: It can be known that occupation with knowledge, behavior, and nutrition status, It can be known that age with knowledge, behavior, nutrition status, occupation density, and residential condition TB infection in children living at the same house with TB patients. However, occupation and age did not similarly affect immunization status.